BER Performance Comparison of Various Modulation Schemes using MMSE on MIMO System over Various Fading Channel - Jyoti,; Nandal, Vikas (International Journal of Computer Sciences and Engineering, 2020)
In MIMO-OFDMA (multiple input multiple output-orthogonal frequency division multiplexing access) when signals are transmitted from the transmitter to receiver different types of error detection techniques are used for calculating the BER (bit error rate), which is an important factor in characterizing the data channel. Among various modulation schemes techniques, MMSE (minimum mean square error) is a versatile technique in which it is not necessary to calculate, explicit the posterior probability density function. In MMSE, we calculate the BER on previously known parameters and no need to assume random variables as a result among all estimators and the accuracy rate is higher. MMSE to reduce BER uses “MINIMUM MEAN SQUARE ALGORITHM” that is MMSE algorithm which is pre-owned to minimize the error and achieved the optimal performance at a cost of high computational complexities.